2016
DOI: 10.2174/1871525714666160407143416
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Genes, Antioxidants and Coronary Artery Disease in Type 2 Diabetes Mellitus

Abstract: The worldwide increasing prevalence of obesity and sedentary lifestyle is the main cause of the rising incidence of T2DM. Due to chronic macrovascular and microvascular complications, T2DM represent a huge socioeconomic burden in the world. Oxidative stress is a key pathogenic mechanism implicated in diabetic coronary artery disease (CAD). Polymorphisms of oxidative stress genes are known to influence oxidative stress levels and are therefore thought to impact CAD pathogenesis. Identifying higher risk groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 154 publications
(225 reference statements)
1
17
1
Order By: Relevance
“…On the other hand, several studies have shown that free radicals cause lipid peroxidation and aggregation of lipid peroxidation products in subjects with diabetes mellitus (7). In addition, the role of genetic susceptibility and epigenetic factors in development of diabetes and its complications has been demonstrated (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies have shown that free radicals cause lipid peroxidation and aggregation of lipid peroxidation products in subjects with diabetes mellitus (7). In addition, the role of genetic susceptibility and epigenetic factors in development of diabetes and its complications has been demonstrated (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…As oxidative stress is recognized as central pathogenic process in accelerated atherosclerosis in T2DM, various studies [7] investigated associations of oxidative stress genes (e.g. Nicotinamide Adenine Dinucleotide Phosphate (NADPH1) oxidase, Myeloperoxidase, Glutathione peroxidase 1, Glutathione Stransferase [30], NAD(P)H1: Quinone oxidoreductase (NQO1), Superoxide dismutase 1 and 2 [31], Thioredoxin reductase 2 [32], Uncoupling protein 2 [33], etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In a physiological system, the imbalance between antioxidant defence mechanism and reactive oxygen species (ROS) production leads to oxidative stress and subsequent pathological conditions [6]. Coronary vascular disease (CVD) occurs as a consequence of accelerated atherosclerosis, mainly driven by oxidative stress [7]. Numerous defence genes are involved in maintaining the balance between oxidant production and their removal by ROS-scavenger enzyme systems.…”
Section: Introductionmentioning
confidence: 99%
“…Type two diabetes mellitus (T2DM) is discussed a major global epidemic leading to loss health in general population [1]. Although the results of recent studies have been well established that overweigh/ obesity and metabolic syndrome are represented the leading risk factor for T2DM and diabetes-related cardiovascular (CV) complications [2][3][4], the impact of the dysmetabolic states on molecular mechanisms regarding vasculature repair systems and "metabolic memory" is not fully investigated [5][6][7]. By now, endothelial dysfunction (ED) has found a key player in increasing CV risk in overweigh/obese and T2DM subjects [8,9].…”
Section: Reviewmentioning
confidence: 99%